2019
DOI: 10.1177/2167479519861704
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotion Regulation and Age in Experiencing Mediated Sports

Abstract: Recent research indicates that sports fanship decreases with age. Socioemotional selectivity theory (SST) posits that older adults, with time limited, shift their focus on positive experiences. Entertainment media choices reflect this proactive emotion regulation strategy. This study applied that perspective to mediated sports content, itself characterized by emotional intensity and unknown outcomes. Using an online survey containing an experimental condition ( N = 433), the current study investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It identifies a number of factors that contribute to diminishing fandom, with some exceptions; it also identifies gender as a factor for maturing fansand in perhaps surprising ways. This study builds on previous research published in the Communication & Sport by Gantz and colleagues over the past decade (e.g., van Driel & Gantz, 2021;van Driel et al, 2019).…”
Section: In This Issuementioning
confidence: 68%
“…It identifies a number of factors that contribute to diminishing fandom, with some exceptions; it also identifies gender as a factor for maturing fansand in perhaps surprising ways. This study builds on previous research published in the Communication & Sport by Gantz and colleagues over the past decade (e.g., van Driel & Gantz, 2021;van Driel et al, 2019).…”
Section: In This Issuementioning
confidence: 68%
“…Understanding the properties of the love–hate measure may assist sports clubs in identifying, preventing and controlling potential fan aggression during games. For instance, recruiting older fans to calm younger fans may help reduce fans' tensions during games, as older fans are less likely to experience intense emotions (van Driel and Gantz, 2019) and tend to be less aggressive than their young counterparts (Toder Alon et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The scholarly evidence supporting either of ESPN’s findings is both limited and mixed (e.g., Wheaton & Thorpe, 2019). A recent study found older adults just as likely to be sports fans as younger adults, but that they consume less sports media and value the outcomes of individual contests less (van Driel & Gantz, 2019). Another study suggested that avid sports fans become even more avid as they age, but that minimal fans’ avidity decreases over time (van Driel, Gantz, & Wenner, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%